Penyelenggaraan Pelindungan Pekerja Migran Indonesia Yang Terinfeksi Virus Human Immunodeficiency Virus Dan Acquired Immunodeficiency Syndrome - Aimatul Millah; Mari Ghoni Al-dzikri (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2023)
Indonesian migrant workers affected by HIV/AIDS face a number of serious challenges in their daily lives. One of the main problems is the lack of understanding and awareness regarding the risk of HIV/AIDS transmission among migrant workers. Apart from that, the sosial stigma against HIV/AIDS is also a serious obstacle for Indonesian migrant workers. Therefore, serious efforts are needed from the government, health institutions and the international community to increase understanding, reduce stigma and increase access of Indonesian migrant workers to health services, including HIV/AIDS prevention and treatment. The aim of protecting migrant workers affected by HIV/AIDS is to protect the human rights of migrant workers affected by HIV/AIDS, including the right to health care, decent work and fair treatment, as well as providing education and information to migrant workers regarding HIV/AIDS, including prevention and treatment methods. This research employs normative research methods. The approaches utilized in this study encompass two conceptual frameworks, namely the statute approach and the conceptual approach ransmission. This study uses normative research methods. Used in this study consisted of 2 (two) conceptual approaches, namely the statute approach and the conceptual approach. The results of this study indicate that the form of protection for migrant workers is protection before work, protection during work, and protection after work. In this case the government also provides forms of legal, sosial and economic protection as well as rehabilitation and sosial reintegration of migrant workers affected by HIV/AIDS.